Model Hipotetik Kegiatan Laboratorium Fisika Untuk Menguatkan Keingintahuan Mahasiswa - M. A. Martawijaya; Eko Hadi Sujiono; Abdul Haris (Seminar Nasional LP2M UNM, 2019)
The hypothetic model is a temporary produced product of a model development process. The hypothetic model in this study is in the form of a model book of physics Laboratory activities to strengthen curiosity with the quality of products assessed using the valuation criteria according to Nieeven which cover the validity of the products developed . The instruments used in this study include a model book assessment of a physics laboratory activity to strengthen curiosity. The students subject to the development target of this hypothetic model are those with the lowest curiosity of each of 1 (one) person based on the public university entrance. The results of this study showed that the hypothetic model of physics laboratory activities to reinforce the curiosity was stated to be very valid by expert assessment after through the process of validation, revision, and focus group Disscussion (FGD joint Validator). So that the hypothetic model of physical laboratory activities is considered valid to strengthen student curiosity